Comparison of methodologies for moisture determination on dried bee pollen samples - Melo,Illana Louise Pereira de (2011)
Bee pollen moisture value is one of the quality parameters for this product. Some countries such as Argentina, Brazil, Bulgaria, Poland and Switzerland have bee pollen regulations on quality parameters, but these are not clear regarding which method should be used for moisture determination. The aim of this paper was to compare six methods of moisture determination in dried bee pollen samples. The methods were: conventional oven at 100 °C, vacuum oven at 70 °C, desiccator with sulfuric acid, drying out process with infrared light at 85 °C, lyophilization and Karl Fisher's method. Based on the results, the best methods for moisture determination of bee pollen were the drying process with infrared and the lyophilization, since these have shown lower moisture values.